Molecular characterization of a Colombian Bacillus thuringiensis strain with activity against Tecia solanivora (Lepidoptera: Gelechiidae) - VILLANUEVA, DIEGO; VELÁSQUEZ, NUBIA; RODRÍGUEZ, ESPERANZA; ORDUZ, SERGIO; ARANGO, RAFAEL (Revista Colombiana de Entomología, 2009)
The Guatemalan potato moth, Tecia solanivora (Lepidoptera: Gelechiidae), is one of the most important pests affecting potatoes in northern South America, causing crop losses ranging from 50 to 100%. In this work, we isolated a native strain of Bacillus thuringiensis (146-15801) with high activity against this moth, and we characterized its Cry genes. This strain was the most active out of eleven strains tested against T. solanivora in laboratory bioassays. Specific PCR and genome walk allowed the isolation of Cry genes showing 99 and 95% similarity to the sequences reported in Cry1Ac and Cry2 genes, respectively. Immunolocation experiments demonstrated that Cry1Ac and Cry2 bind to the midgut epithelial cells, suggest that these two proteins are involved in the insecticidal activity against T. solanivora. Results obtained in this work are relevant because native strains comprise a source of biological components for the development of new bioinsecticides, as well as new Cry genes that can be used for biological control.